High-entropy superparaelectric BNT-KNN-SST ceramic material and preparation method thereof

By introducing Sr(Sc0.5Ta0.5)O3(SST) into BNT-KNN ceramics, high entropy engineering and super-schematic electrical regulation are used to solve the problem of insufficient energy storage density and efficiency of existing ceramic materials under medium electric fields, and high energy storage density, efficiency and long-term stability of high entropy super-schematic BNT-KNN-SST ceramic materials are achieved.

CN119822816AActive Publication Date: 2025-04-15CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510076652.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-15
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing energy storage ceramic materials have insufficient energy storage density, low energy efficiency, and poor high temperature and fatigue resistance under medium electric field conditions, making it difficult to take into account the comprehensive performance and long-term stability.

Method used

By introducing Sr(Sc0.5Ta0.5)O3(SST) into BNT-KNN-based ceramics, high-entropy engineering and super-schematic electrical regulation are used to optimize the local chemical disorder and polarization distortion of the material, building a room temperature super-schematic electrical state, and improving energy storage performance and stability.

Benefits of technology

Ceramic materials with high energy storage density (>7J/cm3) and high energy storage efficiency (>95%) under medium electric fields are achieved, with excellent high temperature stability (20-240°C) and fatigue performance (>106 cycles), significantly exceeding the comprehensive performance of the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822816A_ABST
    Figure CN119822816A_ABST
Patent Text Reader

Abstract

The invention provides a high-entropy superparaelectric BNT-KNN-SST ceramic material and a preparation method of the high-entropy superparaelectric BNT-KNN-SST ceramic material. The general formula of the chemical composition of the ceramic material is (1-x-y) Bi < 0.5 > Na < 0.5 > TiO < 3-x > K < 0.5 > Na < 0.5 > NbO < 3-y > Sr (Sc < 0.5 > Ta < 0.5 >) O < 3 >, wherein x and y are mole percent, x is greater than or equal to 0.2 and less than or equal to 0.3, and y is greater than or equal to 0 and less than or equal to 0.25. According to the technical scheme provided by the invention, the comprehensive performance index of the ceramic material is jointly improved through multiple strategies such as multi-phase coexistence cooperative regulation, high-entropy engineering design, superparaelectric state regulation and defect compensation. The energy storage density of the prepared BNT-KNN-SST-based lead-free energy storage ceramic can reach 8.0 J / cm < 3 > or above in a medium electric field, the energy storage efficiency exceeds 91%, and the highest energy storage efficiency can reach 95.5%. In addition, the material also shows excellent high-temperature stability (20-240 DEG C) and fatigue performance (greater than 106). According to the BNT-KNN-SST-based lead-free energy storage ceramic provided by the invention, high energy storage density, high efficiency and excellent high-temperature and fatigue stability are simultaneously realized in a medium electric field for the first time, and the BNT-KNN-SST-based lead-free energy storage ceramic has important commercial application prospects in the fields of energy storage equipment, power electronics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage, and specifically relates to a high-entropy superparaelectric BNT-KNN-SST ceramic material and a preparation method thereof. Background Art

[0002] In the fields of renewable energy, smart grids and high-performance energy storage devices, ceramic capacitors have attracted much attention due to their fast charging and discharging capabilities and high power density. However, existing energy storage ceramic materials generally have technical problems such as insufficient energy storage density, low energy efficiency, and poor high temperature and fatigue resistance.

[0003] To date, the relatively high energy storage density of dielectric ceramics has almost always been obtained under high breakdown strength (BDS) (>500kV / cm). However, operating capacitors under high electric fields (over ~500kV / cm) not only requires an additional transformer system compatible with dielectric ceramics, but also adds additional risks to the insulation performance of the system, thereby increasing the cost of the system and reducing the safety of the system. Therefore, it is of great practical significance to explore dielectric ceramics with high energy storage density and high energy storage efficiency under moderate electric field conditions (less than ~500kV / cm).

[0004] Energy storage efficiency refers to the ratio of recoverable energy during discharge to total energy stored during charging, which directly reflects the efficiency of piezoelectric materials in the process of converting electrical energy into mechanical energy. High energy storage efficiency means less energy loss during the conversion process, which is crucial for energy storage and conversion applications. However, there are few effective solutions in the prior art that can take into account both comprehensive performance and further improve energy storage efficiency under medium electric field strength. For example, "Realization of superior thermal stability and high-power density in BNT-based ceramics with excellent energy storage performance" discloses the introduction of NaTaO3(NT) into 0.7Bi0.5Na 0.5 TiO3-0.3Sr 0.7 In La0.2TiO3 (BNSLT) ceramics, the content of the highly stable P4bm phase is increased to improve the energy storage density and efficiency. However, the energy storage efficiency of the ceramic material in the article is still less than 90%. Moreover, the energy storage density dropped from 89% to 78% during the cyclic charge and discharge test, and the fatigue stability was insufficient. The inability to further improve the energy storage efficiency and fatigue stability has severely limited the widespread application of energy storage ceramics in the actual industrial field.

[0005] In addition, in some special application scenarios, capacitors need to work in a high temperature environment close to 200°C. So far, the working temperature of most reported energy storage ceramics is below 100-150°C. It can be seen that further improving the high temperature working stability of dielectric energy storage ceramics is also an urgent task.

[0006] In summary, the research aims to explore the potential of a novel battery with high comprehensive energy storage performance, high temperature stability (200°C) and fatigue stability (charge and discharge cycles exceeding 10 6 The energy storage ceramic material with an efficiency of not less than 90% is both a challenge and a technical problem that needs to be solved urgently by those skilled in the art. In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a high entropy superparaelectric BNT-KNN-SST ceramic material. In view of the problems in the prior art, the present invention innovatively introduces Sr (Sc) into BNT-KNN-based ceramics. 0.5 Ta 0.5 )O3(SST), through high entropy engineering and superparaelectric state regulation, significantly improves the comprehensive energy storage performance of the material, especially achieving high energy storage density, high efficiency and excellent high temperature and fatigue stability under medium electric fields, breaking through the technical bottleneck of the existing energy storage ceramic system and providing a new material solution for the commercial application of advanced energy storage devices.

[0008] To achieve the above object, the present invention provides a high-entropy superparaelectric BNT-KNN-SST ceramic material, the specific chemical composition formula is:

[0009] (1-xy)Bi 0.5 Na 0.5 TiO3-xK 0.5 Na 0.5 NbO3-ySr(Sc 0.5 Ta 0.5 )O3; wherein, x and y are molar percentages, 0.2≤x≤0.3, 0≤y≤0.25.

[0010] In a preferred embodiment,

[0011] 0.6Bi 0.5 Na 0.5 TiO3-0.2K 0.5 Na 0.5 NbO3-0.2Sr(Sc 0.5 Ta 0.5 ) The energy storage density of O3 under a medium electric field of 420kV / cm is >7J / cm 3, energy storage efficiency η>95%, temperature stability range is 20–240℃, fatigue resistance>10 6 .

[0012] In a preferred embodiment,

[0013] 0.55Bi 0.5 Na 0.5 TiO3-0.3K 0.5 Na 0.5 NbO3-0.15Sr(Sc 0.5 Ta 0.5 ) The energy storage density of O3 under a medium electric field of 500kV / cm is >8J / cm 3 , energy storage efficiency η>91%, temperature stability range is 20–240℃, fatigue resistance>10 6 .

[0014] Another object of the present invention is to provide a method for preparing a high-entropy superparaelectric BNT-KNN-SST ceramic material, comprising the following steps:

[0015] S1 weigh Bi2O3, Na2CO3, TiO2, K2CO3, Nb2O5 and Sr2CO3, Sc2O3, Ta2O5 according to the stoichiometric ratio;

[0016] S2: weighing raw materials, ethanol and zirconium oxide balls into a ball mill, mixing and ball milling;

[0017] S3 separates the ball-milled slurry and dries it to constant weight to obtain dry powder;

[0018] S4: heating the dried powder to 750-850°C, keeping the temperature for 1-3 hours, cooling it to room temperature, and then crushing and sieving it to obtain a pre-calcined powder;

[0019] S5: adding 0.1-0.2wt% manganese dioxide, ethanol and zirconium oxide balls to the pre-calcined powder, mixing and ball-milling, separating the milled slurry, drying to constant weight, granulating with a polyvinyl alcohol solution with a mass concentration of 4-6wt%, and filtering the obtained powder;

[0020] S6: Press the filtered powder into a ceramic green body, heat it to 550-650℃ to remove binder, heat it to 1130-1180℃ at 3-7℃ / min after cold isostatic pressing, keep it at this temperature for 1-3 hours, and cool it with the furnace;

[0021] S7 polishes the sample, coats high-temperature silver paste on both sides, and keeps it warm.

[0022] In a preferred embodiment, in order to remove moisture from the raw materials and avoid cracking during the sintering process, after weighing all the raw materials, step S1 further includes: drying all the raw materials in an environment of 110-130° C. for 2-4 hours.

[0023] In a preferred embodiment, in step S2, the mass ratio of the raw material, ethanol and zirconia balls is 1:1:2.

[0024] In a preferred embodiment, in step S2, the ball milling speed is 200-600 r / min; and the ball milling time is 6-18 hours.

[0025] In a preferred embodiment, in step S4, the heating rate is 3-7°C / min; preferably, the heating rate is 5°C / min, the temperature is raised to 800°C, and kept at this temperature for 2 hours.

[0026] In a preferred embodiment, in step S5, the mass ratio of the pre-sintered powder, ethanol and zirconia balls is 1:1:2.

[0027] In a preferred embodiment, in step S5, the ball milling speed is 200-600 r / min; and the ball milling time is 6-18 hours.

[0028] In a preferred embodiment, in step S5, using a polyvinyl alcohol solution with a mass concentration of 4-6 wt % for granulation is a conventional method known to those skilled in the art and will not be described in detail here; the mesh size of the sieve used for the filtration is 100 meshes.

[0029] In a preferred embodiment, in step S6, the ceramic green body has a diameter of 8-12 mm, a thickness of 0.5-1.5 mm, and the pressing pressure is 150-250 MPa.

[0030] In a preferred embodiment, in step S6, the heating rate during the debinding treatment is 0.5-1.5°C / min.

[0031] In a preferred embodiment, in step S7, the heat preservation condition includes: heat preservation at 500-700° C. for 5-15 minutes.

[0032] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0033] The present invention combines high entropy ion doping with superparaelectric engineering to innovatively design and modify BNT-KNN-based energy storage ceramic materials. Specifically, it includes:

[0034] The A-site and B-site synergistic high entropy strategy is adopted to introduce Sr 2+ , introduce Sc at position B 3+ and Ta5+ , significantly improving the local chemical disorder and lattice distortion of the system, further inducing local polarization distortion, and optimizing the superparaelectric structure of multiphase coexistence. At the same time, the introduction of KNN realizes The three-phase coexistence state of the material can reduce the maximum dielectric constant temperature (Tm), construct a room temperature superparaelectric state, and significantly improve the energy storage performance and stability. This high entropy structure significantly reduces the dielectric loss of the material while enhancing the energy storage performance. The multi-phase coexistence significantly improves the reversibility of polarization-depolarization and reduces the polarization hysteresis loss, thereby significantly improving the energy storage efficiency. In addition, the use of heterovalent ions (Sr 2 +、Sc 3 + and Ta 5 +) Effectively compensate for the inherent defects and vacancies in the material, thereby significantly improving fatigue resistance and long-term stability.

[0035] The BNT-KNN-SST-based lead-free energy storage ceramics prepared according to the above formula and preparation method can achieve an energy storage density of 8.0 J / cm under a medium electric field. 3 The energy storage efficiency is over 91%, and the highest can reach 95.5%. Moreover, the material not only has excellent energy storage performance, but also exhibits excellent high temperature stability (20-240℃) and fatigue performance (>10 6 ), far exceeding the comprehensive performance of existing energy storage ceramic materials under medium electric fields (300-500kV / cm).

[0036] Therefore, the technical solution provided by the present invention has important commercial application prospects in the fields of energy storage equipment, power electronics, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] These and / or other aspects and advantages of the present invention will become more clear and easier to understand from the following detailed description of the embodiments of the present invention in conjunction with the accompanying drawings, in which:

[0038] Figure 1 The (0.8-x)BNT-0.2KNN-xSST ceramics prepared in Example 1 of the present invention are b The unipolarized PE hysteresis loop and the corresponding energy storage performance under ;

[0039] Figure 2 The fatigue resistance of the 0.6BNT-0.2KNN-0.2SST ceramic material prepared in Example 1 of the present invention;

[0040] Figure 3 The (0.7-x)BNT-0.3KNN-xSST ceramics prepared in Example 2 of the present invention are b The unipolarized PE hysteresis loop and the corresponding energy storage performance under ;

[0041] Figure 4 The fatigue resistance of the 0.55BNT-0.3KNN-0.15SST ceramic material prepared in Example 2 of the present invention;

[0042] Figure 5 The high temperature stability performance of the 0.55BNT-0.3KNN-0.15SST ceramic material prepared in Example 2 of the present invention;

[0043] Figure 6 This is a comparison diagram of the dielectric temperature spectra of the (0.7-x)BNT-0.3KNN-xSST ceramic material prepared in Example 2 of the present invention at 10 kHz. DETAILED DESCRIPTION

[0044] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but it should be understood that the protection scope of the present invention is not limited to the specific implementation methods.

[0045] The embodiment of the present invention provides a high-entropy superparaelectric BNT-KNN-SST ceramic material and a preparation method thereof to solve the technical problem that it is difficult for existing ceramic capacitors to simultaneously achieve high energy storage density, high energy efficiency, high temperature and fatigue stability under medium electric field strength.

[0046] The technical solution of the present invention achieves material performance optimization through the following strategies, thereby solving the above problems.

[0047] 1. Multi-phase coexistence and coordinated regulation: combined with BNT and KNN The three-phase coexistence state optimizes the polarization response and thermal stability of the material.

[0048] 2. High entropy engineering design: By introducing Sr(Sc 0.5 Ta 0.5 )O3(SST), constructing high-entropy components at the A and B sites of the perovskite structure, significantly enhancing the local polarization diversity and the distribution of polar nanoregions (PNRs).

[0049] 3. Superparaelectric state regulation: By inducing the room temperature superparaelectric state, the polarization hysteresis loss of the material is reduced and the energy storage efficiency is improved.

[0050] 4. Defect compensation and enhanced fatigue resistance: using adenovalent ions (Sr 2 +、Sc 3 + and Ta 5 +) Effectively compensate for the inherent defects and vacancies in the material, thereby significantly improving fatigue resistance and long-term stability.

[0051] Through the successful application of the above strategies, the BNT-KNN-SST ceramic material prepared by the present invention can simultaneously take into account the excellent comprehensive performance under medium electric fields, excellent high temperature stability and excellent fatigue resistance. 0.5 Na 0.5 TiO3-0.2K 0.5 Na 0.5 NbO3-0.2Sr(Sc 0.5 Ta 0.5 )O3 ceramics achieved high energy storage density (Wrec>7J / cm) at a medium electric field of 420kV / cm 3 ) and ultra-high energy efficiency (η>95%); 0.55Bi 0.5 Na 0.5 TiO3-0.3K 0.5 Na 0.5 NbO3-0.15Sr(Sc 0.5 Ta 0.5 )O3 ceramics achieved Wrec>8J / cm at a medium electric field of 500kV / cm 3 and η>91%. Moreover, the energy storage performance of the above two ceramic materials remains stable in the range of 20–240℃. 6 After the electric field cycle, the energy storage density and efficiency of the material did not decay significantly, showing extremely strong fatigue resistance.

[0052] The technical solution of the present application is described in detail below through specific embodiments:

[0053] Unless otherwise specified, the technical means used in the present invention are conventional means well known to those skilled in the art, and the various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The reagents used in the present invention are analytically pure unless otherwise specified.

[0054] Example 1

[0055] A high-entropy superparaelectric BNT-KNN-SST ceramic material, the preparation method of which comprises the following steps:

[0056] 1. Raw material weighing: According to the stoichiometric ratio design, weigh 6.051gBi2O 3、 1.835g Na2CO3, 4.149g TiO2, 0.598g K2CO3, 2.301g Nb2O5, 2.556g Sr2CO3, 0.597g Sc2O3, 1.913g Ta2O5. All raw materials were dried at 120°C for 3 hours.

[0057] 2. Mixed ball milling: weigh all the raw materials, ethanol and zirconium oxide balls in a mass ratio of 1:1:2 and put them into a ball mill jar, and mill them at 400 r / min in a planetary ball mill for 12 hours.

[0058] 3. Powder drying: separate the ball material from the slurry after ball milling and dry it to constant weight.

[0059] 4. Pre-sintering: Place the dry powder in an alumina crucible, heat to 800°C in a muffle furnace at a heating rate of 5°C / min, keep warm for 2 hours, and cool to room temperature.

[0060] 5. Secondary ball milling and granulation: Add 0.15 wt% manganese dioxide to the pre-calcined powder, repeat the ball milling process in step 2, and granulate with 5 wt% polyvinyl alcohol solution after drying, and filter through a 100 mesh screen.

[0061] 6. Tablet molding: The granulated powder is pressed at 200 MPa into a ceramic green body with a diameter of 10 mm and a thickness of 1 mm.

[0062] 7. Sintering: Heat the green embryo to 600℃ at 1℃ / min to debind, cold isostatically press (150MPA for 2 minutes), then bury it in ceramic powder with the same composition, heat to 1160℃ at 5℃ / min, keep it at this temperature for 2 hours, and cool it with the furnace.

[0063] 8. Polishing and electrode coating: Polish the sample, apply high-temperature silver paste on both sides by screen printing, and keep it at 600℃ for 10 minutes. 0.5 Na 0.5 TiO3-0.2K 0.5 Na 0.5 NbO3-0.2Sr(Sc 0.5 Ta 0.5 )O3-based BNT-KNN-SST lead-free energy storage ceramics.

[0064] The performance test of the prepared ceramic material showed that: 0.6Bi 0.5 Na 0.5 TiO3-0.2K 0.5 Na 0.5 NbO3-0.2Sr(Sc 0.5 Ta 0.5 ) The energy storage density of O3 under 420kV / cm electric field is 7.02J / cm 3 , the energy storage efficiency is 95.5% (see Figure 1 ), the temperature stability range is 20–240°C. In the fatigue stability test, the test results are as follows Figure 2 As shown in the figure, it can be seen that the prepared 0.6BNT-0.2KNN-0.2SST ceramic material has been6 The energy storage efficiency after cycling is always over 90%.

[0065] Example 2

[0066] A high entropy superparaelectric BNT-KNN-SST ceramic material, compared with Example 1, the only difference is that the composition of the material is:

[0067] 0.55Bi 0.5 Na 0.5 TiO3-0.3K 0.5 Na 0.5 NbO3-0.15Sr(Sc 0.5 Ta 0.5 )O3, and the sintering temperature was increased to 1150°C at a rate of 5°C / min. The rest of the preparation method was exactly the same as that of Example 1.

[0068] The performance test of the prepared ceramic material showed that: 0.55Bi 0.5 Na 0.5 TiO3-0.3K 0.5 Na 0.5 NbO3-0.15Sr(Sc 0.5 Ta 0.5 ) The energy storage density of O3 under 500kV / cm electric field is 8.15J / cm 3 , the energy storage efficiency is 91.3% (see Figure 3 ). In the fatigue stability test, the test results are as follows Figure 4 As shown in the figure, it can be seen that the prepared 0.55BNT-0.3KNN-0.15SST ceramic material has been 6 After cycling, the energy storage efficiency is always over 93% and there is still no downward trend. In the temperature stability test, the test results are as follows Figure 5 As shown, the temperature stability range is 20–240°C. Figure 6 It can be seen that the Tm of 0.55BNT-0.3KNN-0.15SST ceramic material has dropped to room temperature (<25°C), that is, the superparaelectric state at room temperature has been achieved. The successful construction of the room temperature superparaelectric state is the main reason for significantly improving the energy storage performance and stability.

[0069] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A high entropy superparaelectric BNT-KNN-SST ceramic material, characterized in that: The general chemical composition formula of the ceramic material is: (1-xy)Bi 0.5 Na 0.5 TiO3-xK 0.5 Na 0.5 NbO3-ySr(Sc 0.5 Ta 0.5 )O3; wherein, x and y are molar percentages, 0.2≤x≤0.3, 0≤y≤0.

25.

2. The high entropy superparaelectric BNT-KNN-SST ceramic material according to claim 1, characterized in that: 0.6Bi 0.5 Na 0.5 TiO3-0.2K 0.5 Na 0.5 NbO3-0.2Sr(Sc 0.5 Ta 0.5 ) The energy storage density of O3 under a medium electric field of 420kV / cm is >7J / cm 3 , energy storage efficiency η>95%, temperature stability range is 20–240℃, fatigue resistance>10 6 .

3. The high entropy superparaelectric BNT-KNN-SST ceramic material according to claim 1, characterized in that: 0.55Bi 0.5 Na 0.5 TiO3-0.3K 0.5 Na 0.5 NbO3-0.15Sr(Sc 0.5 Ta 0.5 ) The energy storage density of O3 under a medium electric field of 500kV / cm is >8J / cm 3 , energy storage efficiency η>91%, temperature stability range is 20–240℃, fatigue resistance>10 6 .

4. The method for preparing the high entropy superparaelectric BNT-KNN-SST ceramic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1 weigh Bi2O3, Na2CO3, TiO2, K2CO3, Nb2O5 and Sr2CO3, Sc2O3, Ta2O5 according to the stoichiometric ratio; S2: weighing raw materials, ethanol and zirconium oxide balls into a ball mill, mixing and ball milling; S3 separates the ball-milled slurry and dries it to constant weight to obtain dry powder; S4: heating the dried powder to 750-850°C, keeping the temperature for 1-3 hours, cooling it to room temperature, and then crushing and sieving it to obtain a pre-calcined powder; S5: adding 0.1-0.2wt% manganese dioxide, ethanol and zirconium oxide balls to the pre-calcined powder, mixing and ball-milling, separating the milled slurry, drying to constant weight, granulating with a polyvinyl alcohol solution with a mass concentration of 4-6wt%, and filtering the obtained powder; S6: Press the filtered powder into a ceramic green body, heat it to 550-650℃ to remove binder, heat it to 1130-1180℃ at 3-7℃ / min after cold isostatic pressing, keep it at this temperature for 1-3 hours, and cool it with the furnace; S7 polishes the sample, coats high-temperature silver paste on both sides, and keeps it warm.

5. The method for preparing the high entropy superparaelectric BNT-KNN-SST ceramic material according to claim 4, characterized in that: In step S2, the mass ratio of the raw material, ethanol and zirconia balls is 1:1:

2.

6. The method for preparing the high entropy superparaelectric BNT-KNN-SST ceramic material according to claim 4, characterized in that: In step S4, the heating rate is 3-7°C / min.

7. The method for preparing the high entropy superparaelectric BNT-KNN-SST ceramic material according to claim 4, characterized in that: In step S6, the ceramic green body has a diameter of 8-12 mm, a thickness of 0.5-1.5 mm, and a pressing pressure of 150-250 MPa.

8. The method for preparing the high entropy superparaelectric BNT-KNN-SST ceramic material according to claim 4, characterized in that: In step S6, the heating rate during the debinding treatment is 0.5-1.5°C / min.

9. The method for preparing the high entropy superparaelectric BNT-KNN-SST ceramic material according to claim 4, characterized in that: In step S7, the heat preservation conditions include: heat preservation at 500-700° C. for 5-15 minutes.

Citation Information

Patent Citations

  • Potassium-sodium niobate and sodium lithium bismuth titanate-system lead-free piezoelectric ceramic composition

    CN102234195A

  • Ceramic material with high electric energy storage efficiency and preparation method thereof

    CN111170735A

  • Sodium bismuth titanate-based lead-free energy storage ceramic material with high ferroelectric stability and temperature stability and preparation method of sodium bismuth titanate-based lead-free energy storage ceramic material

    CN117383930A

  • Sintered Dielectric Ceramic, Composition for Making, and Use Thereof In Multilayer Capacitor And Energy Storage Device

    US20100008019A1

  • Lead-free piezo-electric porcelain composition, piezo-electric element using the same, and method for producing lead-free piezo-electric porcelain composition

    US20150295162A1